Educação agora é para a vida? A marca social do ensino médio no Brasil. - Ramos, Carlos Alexandre (Universidade Federal de São Carlos, 2005)
This text intends the recognition historic-philosophic of the High School social mark in Brazil. It is understood by social marc from Antonio Gramsci s concept that each social group has its own kind of school, destined to perpetuate in these groups a predetermined traditional, directive or instrumental function. We intend to show as the duality of the Brazilian education was reduced along the years and reflected in the plans, edicts, laws, and High School proposals. The Federal Government supported that the educational reformations occurred since the nineties under the denomination of New High School promoted the unification of the middle school, but, we are going to point out how these reformations deepened even more the education duality and, consequently, of the Brazilian society. It is necessary to investigate the concept of unitary school defended by Gramsci so we understand that the idea of unitary means to overcome the different and far from each other social classes partitions, aiming to eliminate the separation between governor and governed. This proposal does not happen as an immediate and social capitalist tear down structure revolution, but it demands a work of space occupation in the democratic society and in the cultural field, interacting in the political society and in the civil society in the State amplifying gramsciano. It is illusion or cynicism to fetch the unitary school just by the means of documents and laws, or treat it as a mere pedagogical problem, without historizing the concept of education in a socialist perspective and facing it in the social and political clash the possibility of the subaltern classes hegemony construction. Or else, the duality of the education only will be overcome in the perspective of the social and cultural duality surpass. The reformation proposals, including the one called New High School, did not meet these socialist aspirations of a unitary school defended by the educators due to obvious reality: they were neither based on a socialist society project nor foresaw the investment of inaudible resources in the teaching structures. We are also going to denunciate the fragility of the world educational consensus defended by international agencies, which reduce the educational problems to a merely conceptual or pedagogic question. As for this, it is going to be pointed out in the centrality of the strategic speeches of the education in the knowledge society (or postindustrial) its limits and implications. The certainties divulged about the current educational model in the country hide a clear separation among social classes, currently presented with the idea of individual differences generated by the knowledge level of each one, characterizing his/her employability capacity and insertion in the work market. As for it requires an analysis of the difference between educating for the work world and not just for the work market . All in all, the legalist and bureaucratic way with which it is tried to transform the Brazilian education is inefficient and inefficacious. The social mark of the High School was deepened, as well as the class separation. Besides this, in Brazil it is accepted as an almost mechanic link between the education and the citizenship notion, revalidating its sad condition inherited from centuries of discriminatory exclusion and separation between the poor and the rich, between included people and excluded people , between first class citizen and second class citizen.
Keywords: Ensino de segundo grau; Trabalho e educação; Educação brasileira; História da educação; Cidadania; Education in Brazil; High school; Work and education; Citizenship; CIENCIAS HUMANAS::EDUCACAO